My Mexican kitchen : 100 recipes rich with tradition, flavor, and spice - Longoria, Eva, 1975-; Baumann, Thea (Clarkson Potter, 2024)
"A celebration of Mexican ingredients and traditions. While hosting Searching for Mexico on CNN, Eva Longoria reconnected with her Mexican roots and tasted iconic Mexican dishes like meat-stuffed Chiles en Nogada draped in a creamy walnut sauce and the Yucatán classic Pollo Asado, made with an aromatic garlic-citrus-achiote paste. In My Mexican Kitchen, she embraces the techniques and flavors she discovered and brings them home to her Southern California kitchen. From dishes based on long-heeded Aztec traditions like Chicken Enchiladaswith Salsa Verde to her Tia Elsa's Pork and Red Chile Tamales and Conchas that remind her of Mexico City, each recipe offers a delicious tribute to Mexican food and flavors."--